08.06 Circulating exosomes play a role in the regulation of human in vitro osteoclastogenesis. (1st March 2017) - Marton, Nikolett; Kovacs, Orsolya Tunde; Baricza, Eszter; Kittel, Agnes; Gyori, David; Mocsai, Attila; Meier, Florian; Goodyear, Carl S; McInnes, Iain B; Buzas, Edit I; Nagy, Gyorgy
Abstract : Objectives: Exosomes (EXOs) belong to the subcellular sized signalosomes called extracellular vesicles (EVs). EVs, which are present in blood and other bodily fluids, carry a broad spectrum of biomolecules that can influence cellular function. It is conceivable that the vesicle composition of EVs is altered in inflammatory diseases, and that this could contribute to disease pathogenesis. Bone tissue is the second biggest consumer of circulating EVs, but the effect of blood derived EXOs on bone homeostasis has not been described before. Our aim was to study the possible role of circulating EVs on the human in vitro osteoclastogenesis in healthy individuals and in those with active arthritis. Methods: Blood samples of healthy volunteers, rheumatoid arthritis (RA, DAS: 4.79±1.96) according to the 2010 ACR/EULAR classification criteria and psoriatic arthritis (PsA, DAS: 2.79±0.72) patients with peripheral arthritis according to the classification criteria for psoriatic arthritis were collected. EXOs were isolated by gravity filtration and ultracentrifugation. To investigate the properties of EXO samples resistive pulse sensing technique, transmission electron microscopy, and western blot were performed. CD14+ cells were separated from PBMCs with positive selection (StemCell), and the cells were stimulated with 50 ng/ml recombinant human M-CSF, RANKL (PeproTech) and blood-derived EXOs. After 7 days, the cells were fixed and stained for tartrate resistant acid phosphatase (TRAP) (Sigma) and the TRAP positive multinucleated cells were counted. Student's t test and one–way ANOVA with Tukey post hoc test were used as statistical analysis. Results: EXO characterisation revealed the expression of classical exosome markers (i.e., CD9, CD63, flotilin-1, TSG-101) and an average diameter of 100 nm. Healthy (n=11) and RA derived (n=12) EXOs profoundly inhibited osteoclast differentiation (p<0.01), by contrast the PsA derived (n=10) EXOs had a stimulatory effect (p<0.05). In cross-treatment experiments where EXOs and CD14+ cells were interchanged between the 3 groups, healthy (n=5) and RA (n=5) derived EXOs inhibited (p<0.01) the generation of osteoclasts in all groups, while the PsA (n=7) derived EXOs did not have an inhibitory effect. Conclusions: Our abovementioned data suggest that, in a disease-specific manner, circulating EXOs are novel regulators of the human osteoclastogenesis.